Design and implementation of NB-IoT based environmental temperature and humidity monitoring system - Minmin MAO; Jiaqi JU; Yuling OUYANG; Yan JIN (物联网学报)
In view of the disadvantages of the traditional environmental monitoring system, such as high power consumption, high maintenance cost and no real-time monitoring, an environmental temperature and humidity monitoring system based on narrow band Internet of things (NB-IoT) technology was developed, which is mainly controlled by singlechip microcomputer.The work flow of the main controller and the working mode of the communication module were optimized to reduce the power consumption of the system.NB-IoT communication technology was utilized for data transmission to the cloud platform through the base station and core network.China Mobile IoT open platform (OneNET platform) was adopted to achieve the connection between the terminal device and the application, and expanded functions provided by the platform was used to design a mobile phone application to achieve the remote real-time monitoring of environmental parameters and improve the user’s convenience.